2006
DOI: 10.1080/19404476.2006.11462037
|View full text |Cite
|
Sign up to set email alerts
|

Research on Same-Gender Grouping in Eighth Grade Science Classrooms

Abstract: This study examined two hypotheses related to same-gender grouping of eighth grade science classes in a public middle school setting. The hypotheses were (a) male and female students enrolled in same-gender science classes demonstrate more positive science academic achievement than their peers enrolled in mixedgender classes, and (b) same-gender grouping of students has a positive effect on classroom climate. Participants were randomly assigned, and instruction did not vary for the same-gender and mixed-gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…While some researchers found gender grouping to be related to improved levels of girls' attitudes, interest, engagement, and achievement (e.g., Harskamp et al, 2008;), others could not establish such correlations (e.g., Kemp, 2005;) or even revealed reversed relationships (e.g., Gnesdilow et al, 2013). This phenomenon is consistent with what other researchers have noticed (e.g., Friend, 2006). Although small group work has some great advantages, only a relatively small number of studies on gender grouping in STEM fields have been conducted at the small group level.…”
Section: Literature Reviewsupporting
confidence: 92%
See 2 more Smart Citations
“…While some researchers found gender grouping to be related to improved levels of girls' attitudes, interest, engagement, and achievement (e.g., Harskamp et al, 2008;), others could not establish such correlations (e.g., Kemp, 2005;) or even revealed reversed relationships (e.g., Gnesdilow et al, 2013). This phenomenon is consistent with what other researchers have noticed (e.g., Friend, 2006). Although small group work has some great advantages, only a relatively small number of studies on gender grouping in STEM fields have been conducted at the small group level.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Various formats of student activities have been used in these studies, such as paper-andpencil problem solving (e.g., Harskamp, et al, 2005), computer-aided virtual scientific inquiry (e.g., Kemp, 2005), real-life hands-on scientific inquiry (e.g., Estrada, 2007) and engineering design (e.g., Gnesdilow, et al, 2013), or exposure to authentic lab research experiences (e.g., Hirsch, et al, 2014). The term "group" has been used widely in these studies and referred to different units, including pairs (e.g., Harskamp, et al, 2008), small groups (e.g., Gnesdilow et al, 2013), classes (e.g., Friend, 2006), programs (e.g., Richardson et al, 2003), or even camps (e.g., Hughes, et al, 2013). Methods-wise, some researchers simply compared single-gender and mixed-gender units (e.g., Friend, 2006); and a few others systematically varied the gender composition of student units (e.g., 25%, 50%, 75%... female; Dasgupta et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, Friend [Friend 2006] também executou um experimento comparando o desempenho de estudantes do Middle School em aulas de ciências, agrupados por gênero. Neste estudo, os resultados indicam que não houve diferenças significativas no IX Congresso Brasileiro de Informática na Educação (CBIE 2020) Anais do XXXI Simpósio Brasileiro de Informática na Educação (SBIE 2020) desempenho acadêmico dos estudantes do mesmo gênero.…”
Section: Trabalhos Relacionadosunclassified
“…Gneezy, Niederle, and Rustichini (2003), in their test reactions to competition in maths puzzles by boys and girls, concluded that it is not that women are unwilling or unable to perform well in competitions per se, but rather that they do not compete well in competitions against men. The results of Caskey (2006) led to the conclusions that same-gender grouping did not produce significant differences in students' science academic achievement and same-gender classes did not create a more positive classroom climate. Fabian (2009) uncovered through a study that female participation in teaching has positively affected the enrolment of female students in secondary schools in Nigeria at a 5% level of significance.…”
Section: Introductionmentioning
confidence: 97%